SOCIAL CLASS REFLECTED ON TONY MONTANA IN BRIAN DE PALMA’S SCARFACE FILM (1983) - Hafiezd, Rizki Chaidier; Natsir, M.; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research analyze social class as the social phenomena, where social class became life purposes for someone to achieve to be prominent among the society, love and financially. Those phenomenon shows on a film called Scarface, that the researcher uses as the object of the research. From those movie social class portrayed as the most important things to their society life. This research purposed to understand social class on the main character of Scarface movie. This research uses descriptive qualitative method with sociological approach. Sociological approach that researcher uses, was Marx, and Max Weber concept of social class. Which the researcher use to look and identify the condition of the main character on Scarface. The researcher also uses seven tool of character assessment from Literary Element of Characterization from Francis Bacon to dig the reflection of social class on Tony Montana character in Scarface film. Conclusion of this research is The Scarface film, shows social class reflection of how an immigrant from communist Cuba reflected life of his social class and affects his social life in capitalist country The America.